Risk factors for structural and functional progression of primary open-angle glaucoma in an African ancestry cohort. Issue 1 (2nd March 2023) - Salowe, Rebecca J; Chen, Yineng; Zenebe-Gete, Selam; Lee, Roy; Gudiseva, Harini V; Di Rosa, Isabel; Ross, Ahmara G; Cui, Qi N; Miller-Ellis, Eydie; Addis, Victoria; Sankar, Prithvi S; Daniel, Ebenezer; et al.
Abstract : Background/aims: To investigate the rates of structural and functional progression of primary open-angle glaucoma in an African ancestry cohort and identify risk factors for progression. Methods: This retrospective study included 1424 eyes from glaucoma cases in the Primary Open-Angle African American Glaucoma Genetics cohort, with ≥2 visits for retinal nerve fibre layer (RNFL) thickness and mean deviation (MD) measurements over ≥6-month follow-up. The rates of structural progression (change in RNFL thickness/year) and functional progression (change in MD/year) were calculated from linear mixed effects models, accounting for intereye correlation and longitudinal correlation. Eyes were categorised as slow, moderate or fast progressors. Risk factors for progression rates were assessed using univariable and multivariable regression models. Results: The median (interquartile) rates of progression were −1.60 (−2.05 to –1.15) µm/year for RNFL thickness and −0.40 (−0.44 to –0.34) decibels/year for MD. Eyes were categorised as slow (structural: 19%, functional: 88%), moderate (structural: 54%, functional: 11%) and fast (structural: 27%, functional: 1%) progressors. In multivariable analysis, faster RNFL progression was independently associated with thicker baseline RNFL (p<0.0001), lower baseline MD (p=0.003) and beta peripapillary atrophy (p=0.03). Faster MD progression was independently associated with higher baseline MD (p<0.0001), larger cup-to-disc ratios (p=0.02) and lower body mass index (p=0.0004). Conclusion: The median rates of structural and functional progression in this African ancestry cohort were faster than the rates reported from previously published studies in other ethnic groups. Higher baseline RNFL thickness and MD values were associated with faster progression rates. Results highlight the importance of monitoring structural and functional glaucoma progression to provide timely treatment in early disease.